Critical development of green marketing in the hotel industry: Macao case study - Lampo, Alessandro; Gregori, Gian Luca; Cardinali, Silvio; Temperini, Valerio (SGBED Research Symposiums：Doing Well by Doing Good: New Perspectives on Corporate Social Responsibility, Sustainability, and Inclusive Capitalism, 2012)
This study analyzes the green marketing strategies with specific reference to the hotel industry. The concept of green marketing in this sector is crucial due to the growing expected importance of tourism in the future of global economy and its potential impact on social and economic development; this is true particularly in areas with relevant volumes of tourist arrivals. In this sense, we carried out an exploratory research in the hotel industry of the Special Administrative Region (SAR) of Macao in order to: highlight the primary motivations that underlie interventions geared towards the eco-sustainability of hotels, the services they offer and point out the problems, issues, and future prospects in the development of green marketing, as well as explore the role of eco-sustainable values in hotels’ online communication policies. In order to reach these aims a qualitative research was carried out with a semi-structured questionnaire (face-to-face interviews) to a group of hotels. The research was finished by an analysis of their websites, in order to verify possible references to the steps taken to protect the environment.